TEOLOGI LINGKUNGAN HIDUP DALAM PERSPEKTIF ISLAM - Fata, Ahmad Khoirul (ULUL ALBAB Jurnal Studi Islam, 2014)
The damage of nature is believed to be derived from the man, the human mindset who place themselves at the center of this life (anthropocentrism). In this context the teachings of the monotheistic religions are often accused of having a major contribution to the establishment of the doctrine of anthropocentrism paradigm of human superiority over nature. This paper attempts to trace "traces the source of anthropocentrism" in the teachings of Islam in the form of man as a vicegerent on earth. From searches on various texts of Islam (especially the Qur'an), it is known that the position of man as a vicegerent on earth is not a blank check for people to vent all his passion for nature. Humans are created with a variety of advantages which make himself as caliph, but the position was given by God to human beings of all tasks to be assigned. Tasks is what makes the concept of the caliphate on earth does not support exploitative anthropocentrism to nature.